Estrategias metodológicas de comprensión lectora para el aprendizaje significativo de Lengua y Literatura. - Punina Asas, Mauro Vladimir (2022)
The research work is called: "Methodological strategies of reading comprehension for the meaningful learning of Language and Literature" its main objective is to propose methodological strategies of reading comprehension for meaningful learning in the area of Language and Literature of the Educational Unit "Joaquín Lalama," 9th year EGB period 2021 - 2022. The present investigation was carried out with a quantitative approach which favored the collection of data through the Google Forms application, through a questionnaire that was shared with 20 teachers in the area of Language and Literature of the U.E "Joaquín Lalama," the same ones that served for the analysis. In addition, it was possible to reveal the strategies and techniques used by teachers, including playful strategies, prediction strategies, inference, brainstorming, summaries, inferences, and analogies. At the end of the investigation, it was highlighted that the methodological strategies used by the teachers of the U.E "Joaquín Lalama" are basically related to cognitive and metacognitive strategies at an acceptable level, but it is not admissible to promote a higher level of reading comprehension, therefore, Therefore, in the present work, strategies are proposed that will promote significant learning of Language and Literature. In addition, metacognition allows students to develop skills to decode and extract foundations of interest based on previous knowledge. As a result of the research, five strategies are proposed, such as KWL Strategies, Essay Strategies, Graphic Organizer Strategies, Interactive Strategies, and Reading Tree Strategies, based on metacognition, as tools that significantly contribute to the reading comprehension process.